Ketersediaan dan Serapan Mg Kacang Tanah Alfisol dengan Abu Vulkanik Kelud dan Pupuk Organik Amandemen - Suntoro Suntoro; Hery Widjianto; Tutik Handayani (Universitas Sebelas Maret, 2017)
As a result of volcanic eruptions led to the fall of the ash, but there is no much research conducted against nutrient content and the nutrient availability in soil. Disposals of volcanic ash and organic matter are expected fill Mg need in the land. Magnesium In Alfisol is still sufficientless for peanuts. The purpose of this research is study of the impact of volcanic ash and organic fertilizer for the availability and uptake of peanuts Mg in the Alfisol. The experiments did in a greenhouse used completely randomized design with one factor. Data were analyzed with F test rate from 95%, and if the treatments showed significant influenced were continued with rate duncan's multiple range test fence from 95%. The observed variables include the levels of chlorophyll, available Mg and uptake Mg. Research results show that the interaction from treatment chlorophyll content, available Mg and uptake Mg. Based on the findings of the observations of volcanic ash disposals operating significantly impact the availability of magnesium.